2019
DOI: 10.1016/j.ijhydene.2018.08.106
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of thermal hazards from hydrogen under-expanded jet fire

Abstract: Thermal hazards from an under-expanded (900 bar) hydrogen jet fire have been numerically investigated. The simulation results have been compared with the flame length and radiative heat flux measured for the horizontal jet fire experiment conducted at INERIS. The release blowdown characteristics have been modelled using the volumetric source as an expanded implementation of the notional nozzle concept. The CFD study employs the realizable κ-ε model for turbulence and the Eddy Dissipation Concept for combustion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…As shown in Figure 2a, comparing the mass flow rate measured by Acton's experiment [13] with the calculations, the results show that without considering the discharge coefficient (C d = 1.0), the calculated mass flow rates of the two experiments are significantly higher than the measured results. According to the work of Cirrone et al [42], the results via CFD simulation agree with the measured results when the discharge coefficient is equal to 0.7. By adjusting the discharge coefficient from 0.9 to 0.6, the calculated and measured results are compared.…”
Section: Verification Of High-pressure Gas Transient Leakage Modelsupporting
confidence: 70%
See 1 more Smart Citation
“…As shown in Figure 2a, comparing the mass flow rate measured by Acton's experiment [13] with the calculations, the results show that without considering the discharge coefficient (C d = 1.0), the calculated mass flow rates of the two experiments are significantly higher than the measured results. According to the work of Cirrone et al [42], the results via CFD simulation agree with the measured results when the discharge coefficient is equal to 0.7. By adjusting the discharge coefficient from 0.9 to 0.6, the calculated and measured results are compared.…”
Section: Verification Of High-pressure Gas Transient Leakage Modelsupporting
confidence: 70%
“…Jin et al [41] applied ANSYS Fluent to simulate a spontaneous combustion of pressurized hydrogen gas. Cirrone et al [42] used ANSYS Fluent to reproduce the hydrogen jet fire experiments conducted by Proust et al [14]. The thermal hazards of cryogenic hydrogen jet fires were also numerically analyzed by Cirrone et al [43,44], and the performances of three turbulence models, i.e., the standard k − ε, RNG k − ε and realizable k − ε models, were compared.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the blowdown model developed by Molkov et al [23] was implemented. Cirrone et al [28] found that the adiabatic blowdown model provided better agreement with experiment than an isothermal approach for the initial stage of a release, whilst the isothermal blowdown model provided better agreement in the later stages of a release. Thus, an adiabatic blowdown model has been used in this study, as the initial stage of the release is of most interest.…”
Section: Notional Nozzle Model and Blowdown Processmentioning
confidence: 99%
“… Hydrogen Vertical Simulated the flame according to EDC combustion, and DO radiation, Realizable k-ε turbulence models. Cirrone et al. (2019b) CFD code.…”
Section: Introductionmentioning
confidence: 99%